Recubrimientos de hidroxiapatita (HA) depositados porproyecci ́on t ́ermica por combusti ́on (PTC) - Muñoz Medina, Guillermo Arturo (2014)
The thermal spray combustion (PTC) is a technique that is exploring the possibility of depositing biomate-rials as the case of HA, as a new procedure works that are being done are exploratory, so this is a field opento investigation. The HA used in this work was synthesized in specialized laboratories of the University ofAntioquia. The substrate used is Ti-6Al-4V is the most widely used in these applications in biomedicine.